Rising Intonation in the Spanish of Chiloé (Chile): First Approximation [el Habla Ascendente de Chiloé: Primera Aproximación] - Roman-Montes de Oca, D (Pontificia Universidad Catolica de Chile, 2017)
This research paper presents initial findings regarding the analysis of rising intonation contours in final, broad focus declarative utterances recorded in Chiloé (Chile). These utterances-unlike the great majority that have been reported in different varieties of Spanish and characterized by a falling nuclear configuration-exhibit a rising terminal pitch. The first acoustic data of conversational speech are analysed and preliminary phonological observations are made. Acoustic evidence of the rise is included, together with tentative phonolo-gical labelling and, finally, questions are raised and possibilities for further investigation are proposed.1 1 Esta investigación es parte del proyecto Fondecyt N° 1130720, Mapa prosódico de Chile. Descripción fonética y fonológica de rasgos suprasegmentales del español hablado por chilenos, cuyo propósito es realizar un primer mapa audible de la prosodia chilena, de modo similar al del proyecto AMPER (véase, por ejemplo: Dorta, 2007; Fernández Planas, 2005, y Martínez Celdrán, 2011).